The Declaration of Helsinki in relation to Medical Research: Historical and Current Perspectives - Shrestha, B M (Journal of Nepal Health Research Council, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Medical research aims at improving diagnostic, therapeutic and prophylactic measures and understanding of the aetiology and pathogenesis of diseases in humans, and their application to improve the quality of life and survival. The subjects involved are exposed to hazards inherent to the experiments. In order to protect the human subjects and to maintain high ethical standards, the World Medical Association had adopted the â€œDeclaration of Helsinkiâ€ in 1964. The aim of this article is to provide a comprehensive review on the historical and current perspectives on the Declaration of Helsinki in relation to medical research on human subjects. <span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords: ethical issues; Helsinki declaration; human experimentation; therapy; world medical association.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>